Use of tannins to protect insect meal protein against ruminal degradation in sheep - Toral P.G.; González-Rosales M.G.; Hervás G.; Belenguer A.; Mendoza A.G.; Amanzougarene Z.; Fondevila M.; Frutos P. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Due to the high dependence of ruminant feeding systems on the use of soybean meal as source of protein, insect meals have been suggested as a promising alternative. However, a high rumen degradability might be a drawback for its utilisation. In this regard, tannins are known to be able to exert beneficial effects on the digestive utilization of protein-rich feeds due to a reduction of their degradation in the rumen, especially of the protein, although they might also restrict intestinal digestibility. Therefore, this experiment was conducted to examine if tannins could improve the digestive utilization of 4 insect meals (from Acheta domesticus, Alphitobius diaperinus, Tenebrio molitor and Zophobas morio). To this aim, four ruminally cannulated sheep were used to study the ruminal degradation and intestinal digestibility of these feedstuffs as well as those of soybean meal, which was used as a reference. The five substrates were treated with either 0% (control) or 15% DM of commercial tannin extracts from oak (OAK) or quebracho (QUE), and incubated in situ for 16 h. Afterwards, the intestinal digestibility of non-degraded protein was estimated in vitro. Both oak and quebracho tannins were able to protect the protein of insect meals from ruminal degradation, following a similar pattern than that observed in soybean meal. On average, reductions were about 15%, with no significant differences between oak and quebracho effects. On the opposite, the OAK treatment might offer advantages over QUE in terms of intestinal protein digestibility, as the latter caused a lower value in A. domesticus compared with the control. More research would be advisable to confirm these results, particularly in vivo.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)